Noninvasive Ventilation in the Prevention and Treatment of Postoperative Respiratory Disorders - A. Zh. Bayaliyeva; A. V. Pasheyev; R. Ya. Shpaner; R. R. Akhmadeyev (Общая реаниматология)
The paper presents a review of literature on the mechanisms responsible for the development of encephalopathy, such as hemo-dynamic disorders, endothelial damage, apoptosis, and antiapoptosis, in severe concomitant injury without a preponderance of severe brain injury (BI). The proposed markers of the severity of brain damage may be used as components of complex diagnosis of posttraumatic encephalopathy. Key words: concomitant injury, encephalopathy, diagnosis, markers of brain damage.